Efficacy of post-exercise recovery strategies for elite soccer players: a network meta-analysis - Liu, J.; Li, Q.; Han, Y. (Frontiers in Physiology, 2025)
Objective: This study aimed to systematically compare the efficacy of various recovery strategies for improving neuromuscular function, muscle damage, and subjective fatigue in elite soccer players following matches or validated simulations, and to provide evidence-based guidance for clinical practice.